2011
DOI: 10.1590/s0100-39842011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Ecoescleroterapia com espuma no tratamento da insuficiência venosa crônica

Abstract: OBJETIVO: Descrever os resultados da ecoescleroterapia com espuma no tratamento de insuficiência venosa crônica. MATERIAIS E MÉTODOS: Série de casos longitudinal. Entre janeiro de 2007 e novembro de 2009, 18 pacientes com insuficiência venosa crônica foram tratados com ecoescleroterapia com espuma em uma clínica particular. O método de Tessari foi utilizado para produção da espuma e o seguimento dos pacientes variou de 4 a 44 meses. Os desfechos primários foram: oclusão total da veia tratada e reepitelização t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
0
0
1
Order By: Relevance
“…In this study, there was a high rate of retained coagula, observed in 19 (34.5%) patients. Similar results were observed by Ceratti et al, 24 who reported 11%, Nael and Rathbun 25 with 17%, and Kurnicki et al, 26 with 21%. Tremaine et al 27 assessed sclerotherapy in upper limbs and observed a 61.9% rate of retained coagula.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, there was a high rate of retained coagula, observed in 19 (34.5%) patients. Similar results were observed by Ceratti et al, 24 who reported 11%, Nael and Rathbun 25 with 17%, and Kurnicki et al, 26 with 21%. Tremaine et al 27 assessed sclerotherapy in upper limbs and observed a 61.9% rate of retained coagula.…”
Section: Discussionsupporting
confidence: 88%
“…Observou-se, neste estudo, uma alta taxa de coágulos retidos em 19 (34,5%) pacientes. Resultados semelhantes foram encontrados por Ceratti et al 24 , os quais encontraram 11%, Nael e Rathbun 25 , 17% e Kurnicki et al 26 , 21%. Tremaine et al 27 , ao avaliarem escleroterapia em membros superiores, encontraram uma taxa de 61,9% de coágulos retidos.…”
Section: Discussionunclassified